Ultrasonographic Measurement of Cartilage Thickness in Patients With Leprosy - Ercan KARABACAK; Levent TEKİN and Algün POLAT EKİNCİ and Ümüt GÜZELKÜÇÜK and Güzin ÖZARMAĞAN (Archives of Rheumatology, 2014)
Objectives: This study aims to evaluate femoral cartilage thickness in leprosy patients by using ultrasound. Patients and methods: Twenty-one patients previously diagnosed with leprosy (11 males and 10 females), and age, sex and body mass index matched 21 controls were enrolled. Control subjects with a history of any other systemic inflammatory disease and/or knee trauma were excluded. All femoral cartilage evaluations were performed by the same physician who was experienced in musculoskeletal ultrasonography using a linear array probe. Measurements for 42 knees of 21 leprosy patients, and 42 knees of 21 healthy subjects were analyzed. Results: Although patients with leprosy had lower femoral cartilage values than those in the control group, the difference was not statistically significant. Conclusion: We assume that the non-significantly decreased femoral cartilage thickness in patients with leprosy may be explained by the relative immobilization and biomechanical changes arising from complications.